The Children's Education in the Psychological Perspective of Islamic Education - Umam, M.Khotibul; Musthofa, Ihsan (International Journal on Advanced Science, Education, and Religion, 2024)
This research aims to analyze various aspects of children's education and find methods of children's education from the perspective of psychology and Islamic education. This type of research is library research, the data collection technique uses documentation, after the data is collected it is then analyzed using descriptive analysis and content analysis. The research results show that First: the conception of children's education from a psychological perspective has four main dimensions, namely, physical, psychological, spiritual and socio-cultural. Parenting patterns for children's education must be in accordance with the child's psychological condition, namely in an authoritative style. Second: educating with an Islamic education perspective will make children mentally healthier, namely those who have excellent physical condition, high mental intelligence (IQ), mental health conditions/personality that is mature and stable in terms of mental emotionality (EQ) and have personality integrity. who is high (mental-social) and has the strength of faith and Islam. Third: The important role of psychology in Islamic education is to bridge the process of imparting knowledge so that it pays more attention to the psychology of each individual child or student, because this really determines the success of parents or educators in transferring the knowledge given to their children. Keywords: Children's Education, Islamic Education, Education in the Psychological Perspective